De Novo Glomerulonephritis in Simultaneous Pancreas-Kidney Transplantation: A Single Center Experience. (July 2018) - Bösmüller, Claudia; Messner, Franka; Rudnicki, Michael; Neuwirt, Hannes; Oberhuber, Rupert; Margreiter, Christian; Maglione, Manuel; Öfner, Dietmar; Schneeberger, Stefan
Introduction: Concerning the extremely rare complication of de novo Glomerulonephritis (GN) in simultaneous pancreas – kidney transplantation (SPK) we performed a retrospective analysis of kidney and pancreatic graft survival and function, patient survival and major complications in 3 cases of biopsy proven de novo GN after SPK. Patients and Methods: Out of totally 435 SPK performed at our center between 1979 and 2007, three patients (all male, mean aged 28 years) developed a biopsy confirmed de novo Immuncomplex-GN in two and membranoproliferative GN in one case at mean month 118.7 (81–150) posttransplant. No signs of acute or chronic rejection were reported in the histopathological analysis. The primary disease was diabetic nephropathy within type 1 diabetes in all cases. The mean donor age was 39.3 years. The transplantations were performed according to operative standard techniques. The immunosuppression consisted of ATG 8mg/Kg, Tacrolimus (TAC), MMF and steroids. One pancreatic graft was lost at month 1 for thrombosis followed by single pancreas retransplantation being lost for chronic rejection at month 71. The long-term immunosuppression at the time of occurrence of GN consisted of TAC (mean trough level 6.8 ng/ml) and MMF. The indication for biopsy was an increase of serum creatinine (mean 2.6 mg/dL) and proteinuria (mean 3660 mg/l). No critical infectious complication or malignancy occurred before the GN and no patient ever received an mTOR-inhibitor. The therapeutic consequence of the GN was the application of ACE-inhibitor and prednisolone in one patient each. Results and Discussion: After a mean renal long-term survival of 118.6 month post transplant three renal grafts were lost at mean month 17 following biopsy confirmed GN due to the progressive disease. Apart from one pancreas lost already before GN one pancreas failured for chronic rejection at posttransplant month 149 (month 21 post GN) and one pancreas kept an excellent long-term-function within normoglycemia and HbA1c 5.2 g%, free from exogenous insulin. As major complication after GN one case of severe depression is noted. 2 Patients underwent SPK retransplantation and one patient is still in evaluation. Conclusion: The de novo GN after SPK occurred after a long years stable renal function at mean 118 month posttransplant whereby its incidence of 0.007% correlates to the reported inferior limit of (1, 6% - 20%) of de novo GN after single renal transplantation. Trenal grafts were lost at mean month 135.7 posttransplant and at mean month 17 post GN biopsy proven diagnosis for the progredient disease. One pancreatic graft kept an excellent long-term function. A special risk factor for the GN could not be identified. Learning from these cases an early biopsy in case of even mild proteinuria within normal serum creatinine could be favorized. Further series reporting on this very rare complication would be useful in order to learn detailed mechanism of this critical complication.